2003
DOI: 10.1007/s00455-002-0087-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome Following Colon Interposition in Total Pharyngoesophagectomy with or without Laryngectomy

Abstract: Our study compares deglutition between a group who had undergone total esophagopharyngolaryngectomy and a group who had esophagectomy and partial pharyngectomy with preserved larynx, after reconstruction of the upper digestive tract with pedicled colon interposition. In four patients the laryngeal structures could be preserved (three caustic burns and one proximal esophageal tumor). Six patients underwent a total laryngopharyngectomy for large pharyngeal tumors. Swallowing was assessed by a questionnaire, clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…In our study, the free ileocolic flap was found to give excellent results in comparison with other methods. Physiologically, the larger diameter and greater length of a colon graft make it a good choice for restoration of swallowing function at the level of the hypopharynx and the shorter length of jejunum makes sound easily by vibration as a higher pitched tone [4,5]. In our study, all patients except two could initially swallow a semi-solid or solid diet without aspiration (13/15 086.67%).…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…In our study, the free ileocolic flap was found to give excellent results in comparison with other methods. Physiologically, the larger diameter and greater length of a colon graft make it a good choice for restoration of swallowing function at the level of the hypopharynx and the shorter length of jejunum makes sound easily by vibration as a higher pitched tone [4,5]. In our study, all patients except two could initially swallow a semi-solid or solid diet without aspiration (13/15 086.67%).…”
Section: Discussionmentioning
confidence: 60%
“…Free intestinal flap was recognized as impaired swallowing outcome due to considerable amount of residue in the conduit after swallowing [4]. Moerman et al [5] suggested that colon interposition is a reliable reconstruction procedure. The ileocolic flap was designated as small intestine as voice shunt tube and colon as feeding continuity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations